Nominal adjectives in the Ukrainian edition of Church Slavonic language of the end of the XVI – XVII centuries: the pecularities of functioning and declination (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article under consideration analyzes the pecularities of functioning and declination of nominal adjectives of Church Slavonic language of the end of the XVI – XVII centuries. A conclusion about influence of Ukrainian language on these points was made.
Keywords: the Ukrainian edition of Church Slavonic language; nominal adjectives; case forms of adjectives